(untitled) (Medico Legal Update, 2020)
The aim of this study was to study the evaluation of serum oxidation in pregnant women with iron deficiency anemia by measuring lipid oxidation (MDA), and antioxidant status by analogy (Ferritin).Also, Examination of erythropoietin (EPO) levels in pregnancy with iron deficiency anemia. Blood samples were obtained from (80) pregnant women with anemia divided according to the stage of pregnancy and iron deficiency as follows: 20 patients in the second third with anemia without iron deficiency, 20 patients in the second third with anemia with iron deficiency, 20 patients In the third trimester with anemia without iron deficiency, 20 patients in the third trimester have anemia with iron deficiency. In addition to (40) healthy pregnant women as a control group. Divided into two groups, 20 patients in the second trimester and 20 patients in the third trimester. Results: The results show a presence of a significant increase in MDA and EPO in all groups of patients in Iron deficiency in comparison with control group. But, Ferritin levels showed a significant decrease in all groups of patients in Iron deficiency and Iron normal comparison with control group.